Phytosociological Aspects of Some Weed Flora of Post harvested Rice Fields in Shahapur, Bhandara (MS) India - Rao Padmavathi S; Udapure Shweta P (International Journal of Life Sciences, 2017)
Generally weeds are treated as waste plants in crop fields and considered harmful to the crops and eradicated during cultural operations, may be fruitfully utilized to serve the medicinal purposes against diseases. In view of this, Shahapur village near Bhandara is selected for the study of phytosociological aspects of some weed flora in post harvested rice fields. Extensive field survey was conducted two months in post harvested paddy fields during late winter season (Jan.-Mar.). The present survey is useful for the identification of weed species and phytosociological relationships of dominant species. These weeds provide ample opportunities to study them critically for new drug development through chemical analysis without disturbing biodiversity. The probable reasons for the phytosociological relationship of dominant weed species were discussed in the present investigation